School leadership models: what do we know? - Bush, Tony; Glover, Derek (Taylor & Francis, 2014)
The growth in the importance of school leadership has been accompanied by theory development, with new models emerging and established approaches being redefined and further developed. The purpose of this paper is to review current and recent writing on leadership models. The paper examines theoretical literature, to see how leadership is conceptualised, and empirical literature, to demonstrate whether and how the research evidence supports these concepts. The paper shows that leadership models are subject to fashion but often serve to reflect, and to inform, changes in school leadership practice.